SELECTION OF EFFECTIVE BIO - ANTAGONISTIC BACTERIA FOR BIOLOGICAL CONTROL OF TOMATO WILT CAUSED BY FUSARIUM OXYSPORUM F. SP. LYCOPERSICI - B. B. ASHA; S. CHANDRA NAYAKA; A. C. UDAYA SHANKAR; C. SRINIVAS; S. R. NIRANJANA (The Bioscan, 2011)
Bacteria from the rhizoplane soil and surrounding soil of healthy and Fusarium oxysporum diseased tomato plants of district regions of Karnataka were collected. The best bacterial strains, based on their ability to control development of Fusarium oxysporum isolate, were identified as BS1, BS5 and BS18. All bacterial isolates resulted effective for the in vitro control of growth of Fusarium oxysporum, where the control mechanisms used by the bacteria do not involve the secretion of fungal cell wall hydrolytic enzymes. On the other hand, all bacteria grew well in conditions similar to those that can be found at the field level (considering pH, salinity, Fe3+and temperature) and showed a good capacity of tomato root colonization. These results suggest that Pseudomonas fluorescens isolates studied have an excellent potential to be used as biocontrol agents of Fusarium oxysporum in tomato greenhouses at the field level.